CYP3A Excipient-Based Microemulsion Prolongs the Effect of Magnolol on Ischemia Stroke Rats - Jiun-Wen Guo; Chih-Cheng Chien; Jiann-Hwa Chen (Pharmaceutics, 2020)
Magnolol, which is a CYP3A substrate, is a well-known agent that can facilitate neuroprotection and reduce ischemic brain damage. However, a well-controlled release formulation is needed for the effective delivery of magnolol due to its poor water solubility. In this study, we have developed a formulation for a CYP3A-excipient microemulsion, which can be administrated intraperitoneally to increase the solubility and bioavailability of magnolol and increase its neuroprotective effect against ischemic brain injury. The results showed a significant improvement in the area under the plotted curve of drug concentration versus time curve (AUC0–t) and mean residence time (MRT) of magnolol in microemulsion compared to when it was dissolved in dimethyl sulfoxide (DMSO). Both magnolol in DMSO and microemulsion, administrated after the onset of ischemia, showed a reduced visual brain infarct size. As such, this demonstrates a therapeutic effect on ischemic brain injury caused by occlusion, however it is important to note that a pharmacological effect cannot be concluded by this study. Ultimately, our study suggests that the excipient inhibitor-based microemulsion formulation could be a promising concept for the substrate drugs of CYP3A.